1999
DOI: 10.1111/j.1479-828x.1999.tb03145.x
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and Cirrhosis of the Liver

Abstract: Pregnancy in patients with cirrhosis of the liver is uncommon. We reviewed 9 pregnancies in 7 patients with cirrhosis. One patient conceived within 1 month of diagnosis and in another the disease was diagnosed during the index pregnancy. Four patients has associated portal hypertension and 1 of them conceived after lienorenal shunt. Complications associated with these pregnancies were jaundice (1) jaundice plus ascites (2) and gastrointestinal bleeding (1). In 2 patients endoscopic sclerotherapy was done durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 8 publications
0
65
0
6
Order By: Relevance
“…Pregnancy in liver cirrhosis is rare, and, when it occurs, the risk of hepatic decompensation is high. 13,14 In a recent study the overall maternal complication rate in patients with autoimmune hepatitis was ≈40%. 15 Women with cirrhosis had the highest risk of complications, including hepatitis flare and liver decompensation, but preeclampsia was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy in liver cirrhosis is rare, and, when it occurs, the risk of hepatic decompensation is high. 13,14 In a recent study the overall maternal complication rate in patients with autoimmune hepatitis was ≈40%. 15 Women with cirrhosis had the highest risk of complications, including hepatitis flare and liver decompensation, but preeclampsia was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…11 Cirrhotic patients have a high risk of liver decompensation because of worsening synthetic liver function, development of ascites, and hepatic encephalopathy. 8 Maternal mortality rate as high as 10.5% has been described in this group. 12 Maternal prognosis depends on the degree of hepatic dysfunction during pregnancy rather than its cause.…”
Section: Pulse Volume 5(1)2011mentioning
confidence: 78%
“…Anticipating PPH from atonic uterus in already debilitating patient, total abdominal hysterectomy (TAH) was done, abdomen closed with three drain tube kept in situ (one sub-hepatic, one in peritoneal cavity & another in sub-rectal space When pregnancy is successful in a cirrhotic woman, spontaneous abortion rate, risk of prematurity, and perinatal death rate are all increased. 8 Review of literature has shown that there is 10-15% risk of abortion in early pregnancy 9,10 and 45 out of 69 babies born to cirrhotics survived in the neonatal period. 11 Cirrhotic patients have a high risk of liver decompensation because of worsening synthetic liver function, development of ascites, and hepatic encephalopathy.…”
Section: Pulse Volume 5(1)2011mentioning
confidence: 99%
“…Tuttavia alcune recenti ricerche suggeriscono che la CP è una malattia vascolare, innescata dalla secrezione di potenti fattori anti angiogenetici dalla placenta e dall'ipofisi. 83 Questa ipotesi è stata già avanzata in passato, ma le dimostrazioni sperimentali a sostegno ci sono state offerte solo di recente. In particolare modo uno squilibrio dei fattori angiogenetici sistemici 84 è stato verificato nei topi mancanti di PGC-1 alfa, un regolatore di fattori pro angiogenetici come il VEGF.…”
Section: Eziopatogenesi Della Cardiomiopatia Peripartumunclassified
“…82 Quando inizia comunque una gravidanza in una donna cirrotica, il tasso di aborti spontanei, il rischio di prematurità e il tasso di mortalità perinatale sono tutti aumentati. 83 Le pazienti con cirrosi alcolica hanno un alto rischio di scompenso epatico a causa del peggioramento della funzione di sintesi epatica, di sviluppo di ascite ed encefalopatia epatica, di un alto tasso di mortalità materna durante la gravidanza. 84,85 L'ipertensione portale peggiora durante la gravidanza, a causa di un aumento del volume ematico e di un aumento della resistenza vascolare per compressione esterna della vena cava inferiore da parte dell'utero gravido.…”
Section: Epatopatia Alcolicaunclassified